Model Pendidikan Karakter di Madrasah Diniyah Takmiliyah dalam Pembentukan Karakter Santri - Siti Makrupah (EDU-RELIGIA : Jurnal Keagamaan dan Pembelajarannya, 2021)
Character education is an important thing to be instilled in the younger generation where parents, educators, religious institutions, youth organizations and others, have a great responsibility to build character, values, and morals in the younger generation. This type of research uses a qualitative descriptive approach. The reason for using descriptive research with a qualitative approach is to raise the facts found in the field and present them as they are. According to Arikunto, descriptive research is research that is intended to collect information or the status of existing symptoms, namely the state of symptoms according to what they were at the time the research was conducted. The results showed that the character learning model applied at MDTA Hidayatun Nasyi'in, Bulurejo Village, Rengel Subdistrict, was divided into two parts, namely religious and vocational. Religious learning through various strategies, approaches, methods, and models that are able to form positive characters, while vocational learning essentially gives students freedom, to implement a number of desired characters; confident, independent, disciplined, honest, and religious based on the results of observations and general analysis of the MDTA ustad/dzah MDTA Hidayatun Nasyi'in in the aspect of method that has met the criteria and is able to use methods that are in accordance with the material, able to direct students so that they can be motivated, for example by there are rewards and punishments. It can be concluded that the use of evaluation as a measure of success in order to achieve the target that is the goal has been used properly, the application of the types of assessments carried out in the form of performance appraisals, portfolios, written tests, oral and practical tests